U-Pb zircon dating of basement inliers within the Moine Supergroup, Scottish Caledonides: implications of Archaean protolith ages. - Friend, C.; Strachan, R.; Kinny, Peter (Geological Society Publishing House, 2008)
Basement gneiss inliers within the Scottish Caledonides have been conventionally correlated with the Archaean Lewisian Gneiss Complex of the Caledonian foreland. Alternatively, the inliers could represent allochthonous terranes accreted to Laurentia before or during the Caledonian orogeny. SIMS U-Pb zircon dating indicates that the Ribigill, Borgie, Farr and Western Glenelg basement inliers are characterized by late Archaean protolith ages, and a period of isotopic disturbance in the late Palaeoproterozoic. The data are broadly consistent with correlation between the inliers and components of the Lewisian Gneiss Complex of the Caledonian foreland. The c. 2900 Ma protolith ages support correlation of the Borgie and Farr inliers with the Assynt terrane, and a younger, c. 2800 Ma age for the Ribigill inlier supports correlation with the Rhiconich terrane.None of the studied inliers shows a complete match of protolith and early metamorphic histories with any of the Lewisian basement terranes, but differences between the inliers and the foreland are no greater than those recorded within the foreland basement terranes themselves. Therefore, it remains probable that the dated inlier gneisses formed a distal part of the Laurentian margin prior to final telescoping during the Caledonian orogeny.